Предельный переход в системах линейных дифференциальных уравнений - Михайлец, В.А.; Рева, Н.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The limit theorems for the solutions of linear matrix differential equations in the Sobolev’s Wn,p-norms are established. The case of the uniform C-norm was studied earlier by many authors in detail. Some applications are given.